3D-aligned tetrameric ion channels with universal residue labels for comparative structural analysis - Tikhonov, Denis B.; Korkosh, Vyacheslav S.; Zhorov, Boris S. (Biophysical journal, 2025)
Despite their large functional diversity and poor sequence similarity, tetrameric and pseudotetrameric potassium, sodium, calcium, and cyclic-nucleotide gated channels, as well as two-pore channels, transient receptor potential channels, and ionotropic glutamate receptor channels, share a common folding pattern of the transmembrane (TM) helices in the pore domain. In each subunit or repeat, two TM helices connected by a membrane-reentering P-loop contribute a quarter to the pore domain. The P-loop includes a membrane-descending helix, P1, which is structurally the most conserved element of these channels, and residues that contribute to the selectivity-filter region at the constriction of the ion-permeating pathway. In 24-TM channels, the pore domain is surrounded by four voltage-sensing domains, each with conserved folding of four TM helices. Hundreds of atomic-scale structures of these channels, referred to as “P-loop channels,” have been obtained through x-ray crystallography or cryoelectron microscopy. The number of experimental structures of P-loop channels deposited in the PDB is rapidly increasing. AlphaFold3, RoseTTAFold, and other computational tools can be used to generate three-dimensional (3D) models of P-loop channels that lack experimental structures. While comparative structural analysis of P-loop channels is desirable, it is hindered by variations in residue numbers and 3D orientations of the channels. To address this problem, we have developed a universal residue-labeling scheme for TM helices and P-loops. We further created a database of P-loop ion channels, PLIC: www.plic3da.com, which currently includes over 400 3D-aligned structures with relabeled residues. We use this database to compare multiple 3D structures of channels from different subfamilies. The comparison, which for the first time employs statistical methods, highlights conserved and variable elements in the channels' folding, reveals irregularities, and identifies outliers that warrant further analysis.